2023
DOI: 10.1039/d3qm00662j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in designing solid-state electrolytes to reduce the working temperature of lithium batteries

Zhicheng Yao,
Yutong Wang,
Shuang Wan
et al.

Abstract: Although lithium-ion battery (LIB) has excellent performance, it has some defects such as poor safety performance and low energy density. Solid-state battery (SSB) is widely concerned because of its intrinsically...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 165 publications
0
8
0
Order By: Relevance
“…A primary challenge in using lithium-metal anodes is the formation of lithium dendrites during cycling, leading to potential short circuits and battery failure, as noted in A primary challenge in using lithium-metal anodes is the formation of lithium dendrites during cycling, leading to potential short circuits and battery failure, as noted in ref. [166]. This dendritic growth, along with chemical and electrochemical instability and chemomechanical expansion, creates significant barriers to the commercialization of SSBs.…”
Section: Anode Materials Selection For Ssbsmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary challenge in using lithium-metal anodes is the formation of lithium dendrites during cycling, leading to potential short circuits and battery failure, as noted in A primary challenge in using lithium-metal anodes is the formation of lithium dendrites during cycling, leading to potential short circuits and battery failure, as noted in ref. [166]. This dendritic growth, along with chemical and electrochemical instability and chemomechanical expansion, creates significant barriers to the commercialization of SSBs.…”
Section: Anode Materials Selection For Ssbsmentioning
confidence: 99%
“…This dendritic growth, along with chemical and electrochemical instability and chemomechanical expansion, creates significant barriers to the commercialization of SSBs. To address these issues, Yao and colleagues [166] concentrated their research on designing solid-state electrolytes that operate at reduced temperatures. Their findings suggest that lower operational temperatures in SSBs can greatly improve the stability and effectiveness of lithium-metal anodes, thereby reducing the risks associated with dendrite formation and other instabilities.…”
Section: Anode Materials Selection For Ssbsmentioning
confidence: 99%
“…1) To improve the low-temperature conductivity of the electrolyte by optimizing the composition of the solvent and using new electrolyte salts; 2) To use new additives to increase the conductivity of lithium ions at low temperatures. [36] In 2003, Yuriy et al [37] reported a new generation of lithiumsulfur rechargeable batteries based on specially designed electrolytes. The extraordinary experimental data of LiÀ S batteries in the low-temperature performance was worth noting.…”
Section: Electrolytementioning
confidence: 99%
“…Generally, LIBs used in electric vehicles and wearable portable electronic devices typically operate at temperatures between −20 and 40 °C . In particular cases, there are some ultralow temperature application scenarios below −30 °C, such as ultralow temperature electric vehicles in variable climates, polar scientific expedition, military equipment exposed to ultralow temperature, etc., , which pose increasingly severe challenges to the operation of batteries. , In ultralow temperature situation, the conduction of lithium ions in LIBs is severely hindered, resulting in a significant decrease in performance.…”
Section: Introductionmentioning
confidence: 99%